Beyond the Formal-Informal Dichotomy: Towards Accommodating Diverse Milk-Collection Practices in the Economic Middle of Kenya’s Dairy Sector - Vernooij, Vera; Vellema, Sietze R.; Crane, Todd A. (Informa UK Limited, 2023)
The triangle of dairy intensification, commercialisation and market formalisation is promoted to address the challenges of food and nutrition security (FNS) and climate change. This article questions the need for formalisation to reach intensification and commercialisation objectives in Kenya. Moving beyond the binary perception of milk markets as either 'formal' or 'informal', we investigate a repertoire of milk-collection practices and address the following question: 'What enables diverse intermediary practices to ensure a consistent flow of milk from grass to glass?' Sampling, data collection and analysis were guided by a qualitative research design for an empirical exploration of the practices of owner-operated (N = 13) and corporate (N = 4) milk collectors. Iterative analysis of observations revealed three main themes constituting milk-collection practices: (1) buying milk, (2) managing milk (quantity and quality measurement) and (3) selling milk to the next buyer. These practices were enabled and sustained by the diverse options available for each aspect of milk collection, and by the capacity of collectors to accommodate variety in their practices. We invite scholars and practitioners to conduct deeper explorations of how to accommodate events in practice to enhance the success of ambitions relating to FNS and climate change through pathways of intensification and commercialisation.